2011
DOI: 10.1021/cs2000472
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Carbon Resistance of Ni-Based Steam Reforming Catalyst by Alloying with Rh: A Computational Study Coupled with Reforming Experiments and EXAFS Characterization

Abstract: Supported nickel catalysts are widely used in hydrocarbon steam reforming for producing hydrogen. Carbon deposition is a major cause of Ni catalyst deactivation. In this work, supported Ni and Ni/Rh catalysts were synthesized and tested for liquid hydrocarbon steam reforming. Carbon analysis on the spent catalysts illustrates that the carbon deposition is significantly reduced with inclusion of Rh. Extended X-ray Absorption Fine Structure (EXAFS) analysis indicates close interactions between Ni and Rh atoms. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 64 publications
3
39
0
Order By: Relevance
“…Consequently, enhanced activities were reported not only in conventional and commercial H 2 and syngas processes such as steam reforming [17,18], autothermal reforming [7,12,17,19,20] and oxyreforming [21][22][23][24], but also in more prone to carbon formation processes such as dry reforming [9,[25][26][27][28][29][30][31], ethanol reforming [32][33][34], biogas reforming [35] and, lastly, in fuel cell devices [17], in which large hydrocarbons were fed in systems operating under transient conditions [36,37]. Indeed, Rh promoted the gasification of adsorbed carbon by steam in the autothermal reforming of isooctane [38] and decreased carbon formation in the reforming of liquid hydrocarbons [39]. Moreover, Rh improved sulphur tolerance during steam reforming of methane [40] or S-containing liquid fuels [41].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, enhanced activities were reported not only in conventional and commercial H 2 and syngas processes such as steam reforming [17,18], autothermal reforming [7,12,17,19,20] and oxyreforming [21][22][23][24], but also in more prone to carbon formation processes such as dry reforming [9,[25][26][27][28][29][30][31], ethanol reforming [32][33][34], biogas reforming [35] and, lastly, in fuel cell devices [17], in which large hydrocarbons were fed in systems operating under transient conditions [36,37]. Indeed, Rh promoted the gasification of adsorbed carbon by steam in the autothermal reforming of isooctane [38] and decreased carbon formation in the reforming of liquid hydrocarbons [39]. Moreover, Rh improved sulphur tolerance during steam reforming of methane [40] or S-containing liquid fuels [41].…”
Section: Introductionmentioning
confidence: 99%
“…The coordination energies of the CH-Pd2 and CH-Pd2O systems were increased to −5.70 and −4.66 eV, respectively. These results indicated that the coordination energy decreased with the cracking process: CH4 < CH3 < CH2 < CH < C [26,37,38]. They also revealed that the interaction between CHx (x = 0-4) and the catalyst was reduced by the introduction of the oxygen atom.…”
Section: System Coordination Energy Pd2 (Ev) Pd2o (Ev)mentioning
confidence: 87%
“…As shown in Figure 2 and Table 1, CH 4 dissociation catalyzed by Pd 2 and Pd 2 O results in an exothermic formation of CH 4 -Pd 2 and CH 4 -Pd 2 O systems. In the CH 4 -Pd 2 system, the length of the C-Pd bond was 2.657 Å, while the length decreased to 2.432 Å in CH 4 -Pd 2 O [37]. The coordination energy of the two systems was -0.34 and -0.87 eV, respectively.…”
Section: System Coordination Energy Pd2 (Ev) Pd2o (Ev)mentioning
confidence: 93%
See 1 more Smart Citation
“…For example, decorating La 1-x Sr x Co 1-y Fe y O 3-ÎŽ (LSCF) porous electrodes with certain nanoparticles such as Sm 1-x Sr x CoO 3-ÎŽ (SSC) and Ce 1-x Sm x O 2-ÎŽ (SDC) has been reported to reduce polarization resistances [26,27], whereas coating LSCF surfaces with La 1-x Sr x MnO 3-ÎŽ (LSM) can improve long-term stabilities [28]. Carbon deposition on nickel-based anodes can also be alleviated through modifications such as BaO, BZCYYb, or BZY, which are catalysts that can facilitate the gasification of deposited carbon atoms [3,9,29,30].…”
Section: Introductionmentioning
confidence: 99%